The Influence of the Learning Model (Quantum Learning) in Sociology Subject Phase E on Student Learning Outcomes at SMAN 1 Suliki - Aisyah Rasyidah; Sri Rahayu; Yanti Sri Wahyuni (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study was motivated by the low academic achievement of 10th-grade students in the sociology course. This is evident from the final exam scores for the first semester of the 2024/2025 academic year. The purpose of this study is to determine the effect of using the quantum learning model in the sociology course (Phase E) on student learning outcomes at SMAN 1 Suliki. The method used in this study was a quantitative method with a quasi-experimental design. The research data obtained showed that the normality test was conducted using SPSS with the Shapiro-Wilk test; since the sample size was 36 < 50, the results of the normality test indicated that the Shapiro-Wilk values for the control and experimental classes were < 0.05, the control class pretest was 0.031, the control posttest was 0.034, and the experimental class pretest was <0.001, while the experimental posttest was 0.003; the data were categorized as non-normal. In the homogeneity test, the data showed that the mean was <0.05 (0.017 < 0.05), so the data was categorized as non-homogeneous. Meanwhile, in the results of the hypothesis test conducted using the Mann-Whitney Test, we can see that the Asymp.Sig (2-tailed) was <0.05 (specifically <0.001), indicating a significant difference between the control and experimental classes. Since the result of the Asymp.Sig (2-tailed) test is when the Asymp.Sig (2-tailed) value is less than 0.05, it can be concluded that the use of the quantum learning model has an effect on student learning outcomes at SMAN 1 Suliki.